Exploring English Education Students’ Self-Efficacy in Utilizing AI Tools for Language Learning - Anggrainy, Septy (IJLHE: International Journal of Language, Humanities, and Education, 2025)
This study explores English Education students’ self-efficacy in utilizing Artificial Intelligence (AI) tools for language learning within the Indonesian higher education context. A sequential explanatory mixed-method design was employed. In the first phase, a quantitative descriptive survey was administered to 100 English Education students using an adapted version of the Teacher Artificial Intelligence Competence Self-efficacy (TAICS) scale. The instrument consisted of twenty items covering six constructs: AI Knowledge, AI Pedagogy, AI Assessment, AI Ethics, Human-Centred Education, and Professional Engagement. Descriptive statistical analysis revealed that students’ overall self-efficacy was at a moderate level (M = 3.53), with the highest confidence observed in AI Knowledge and AI Pedagogy, while AI Ethics and Professional Engagement scored lowest. In the second phase, qualitative data were collected through semi-structured interviews with a purposive sub-sample of fifteen students and analyzed thematically. Five themes emerged: mastery experiences, vicarious experiences, social persuasion, ethical awareness, and affective states. These themes reflected the sources of self-efficacy proposed by Bandura and explained variations in students’ confidence. The findings indicate that students are generally prepared to integrate AI tools for learning and future teaching, yet gaps remain in ethical confidence and professional engagement. The study suggests that teacher education programs should provide structured training, reflective practices, and ethical guidance to strengthen responsible AI use.